(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Tidal inundation has progressively impacted coastal residential areas in Kelapa Lima District, Kupang City, as a consequence of sea-level rise, accelerated urban expansion, and insufficient drainage infrastructure. Notwithstanding the recurrence of flooding incidents, a spatially integrated vulnerability evaluation for this locality has not yet been systematically established. This research seeks to examine the degree of vulnerability within coastal settlements by applying a Geographic Information System (GIS)-driven multi-criteria spatial methodology. Physical variables (elevation, proximity to the coastline, slope gradient, and land utilization) were synthesized with a social indicator (population density) through procedures of scoring, normalization, and weighted assessment techniques. Spatial synthesis was conducted using weighted overlay analysis within a GIS environment to generate vulnerability zoning maps. The findings categorize the coastal territory into three levels of vulnerability: non-vulnerable (24%), vulnerable (46%), and highly vulnerable (30%). Roughly 76% of the investigated area is situated within zones classified as vulnerable. Field verification demonstrates the correspondence between the spatial simulation results and the actual occurrence of tidal flooding events. The principal contribution of this study resides in the incorporation of spatial and socio-environmental indicators within a GIS-oriented analytical framework to inform adaptive coastal planning and mitigation measures.